PENERAPAN PROJECT BASED LEARNING TERINTEGRASI AJARAN TRI N UNTUK MENINGKATKAN KREATIVITAS SISWA DALAM PEMBELAJARAN BAHASA INDONESIA - Esti Utami; Siti Rochmiyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Learning carried out in the independent curriculum era should develop student creativity so that students are able to create something different to face the competition in real life that students will experience. However, the Indonesian language learning that occurs at SD Negeri 1 Banjareja has not been able to develop creative attitudes in students. For this reason, it is necessary to carry out learning innovations that can equip students with creative attitudes by implementing project based learning that integrates Tri N teachings in Indonesian language learning so that students' creativity grows and develops. This research aims to increase student creativity and find out how to increase student creativity in learning Indonesian by implementing project based learning that integrates Tri N teachings for class V students at SD Negeri 1 Banjareja. The research method used in this research is descriptive qualitative, which describes the application of Tri N teachings through project based learning syntax in class V Indonesian language learning at SD Negeri 1 Banjareja. Qualitative data analysis is carried out through the stages of reducing the collected data, data exposure, and data conclusion. The results of the research carried out show that there has been an increase in creativity in students, as evidenced by the works or learning products produced which are innovative works, which have their own characteristics between one work and another. Apart from that, the implementation of the project based learning model can be carried out according to the syntax by integrating the Tri N teaching steps in it. The integration between project based learning and Tri N teachings is mutually supportive and strengthening so that this research is successful.